Triagem fitoquímica e avaliação da sensibilidade antimicrobiana e da genotoxicidade de Sedum praealtum DC. (Bálsamo) - Marques, Milene Bueno (2015)
Sedum praealtum DC. (Crassulaceae) is one of 350 species pharmacologically active from the genus Sedum, whose actions in treatment of eyes (pain and swelling) and ulcer, inflammatory problems, as contraception and anti-fertilization, antinociceptive and anti-inflammatory have been reported. The objective was to evaluate the hydroethanolic extract of S. praealtum regarding their potential antimicrobial in vitro (some bacteria, yeasts and micobactéria strains), cytotoxic in vitro and genotoxic in vivo. A fast phytochemical screening of this extract was also performed. The antimicrobial activities were carried out by microdilution in broth and agar diffusion methods (CLSI). The genotoxic effects and systemic toxic and cytotoxicity were evaluated by micronucleus assay in mice bone marrow and cell cultures of Aedes albopictus, respectively. The selectivity index was also established (SI = CI50/MIC). Dosages of flavonoids and phenolic compounds were done by colorimetric and precipitation techniques. A high amount of phenolic compounds were identified in S. praealtum root. The S. praealtum leaves showed broad spectrum of action and variables MICs: Gram-negative bacteria (E. aerogenes, E. coli, P. aeruginosa, P. mirabilis, S. marcescens and S. typhimurium), gram-positive (B. cereus, B. subtilis, E. faecalis, M. luteus and S. aureus) and yeast (S. cerevisiae). The stem and root were restricted to gram-positive bacteria and S. cerevisiae, other than E. coli (stem) and P. mirabilis (root) microbicidal action microorganism- and anatomical part-dependent (leaf, stem or root). S. praealtum showed no inhibition against C. albicans, M. tuberculosis and M. bovis. The root showed acceptable SI (SI  1) for P. mirabilis; B. subtilis; B. cereus; M. luteus; E. faecalis; S. aureus and S. cerevisiae, whereas the sheet only for S. cerevisiae. The hydroalcoholic extract of S. praealtum leaves revealed no genotoxic effects (no clastogeny and/or aneugeny) and toxicity in bone marrow of mice, dose (0.5-2 g.Kg-1) and time-independent (24-48 hours), but sex-dependent (male and female). This was the first scientific study of this nature involving S. praealtum and partially the results provide a theoretical basis for comprehensive development and utilization of plant resources. However, advanced phytochemical characterization together with the various pharmacological and pharmacogenomic studies should be conducted in order to characterize their effects and, importantly, for the establishment of limits for human consumption, the delineation of potential risks to human health, and for rational strategies for implementing chemo-preventive measures.